Projections of the population size of Russia and the world - P. Zozulya; A. Zozulya (Вестник университета)
The article presents forecasts of the population of Russia and the world in General. Highlighting three variants of the forecast of a demographic situation in Russia before 2050 yr. The article presents a forecast change in population by category (male, female, able-bodied population). It is concluded that the main growth of the population to 2050 yr. will be at the expense of labour migration, primarily from CIS countries. The analysis of trends in population to 2050 yr. in different countries and continents as a whole. Presents the forecasted share of elderly population of the continents of the world in 2050 yr. conclusions about the population decline of the highly developed European countries, and the increase in the number of developing.